Exploring the effect of external shame on body appreciation among Portuguese young adults: The role of self-compassion - Marta-Simões, Joana (2016)
Studies on body image-related disturbances have recently embraced a fresh and innovative construct: body appreciation. Body appreciation, an aspect of positive body image, defines as the detention of a balanced, affectionate and health-conscious relationship with one’s own body’s features. Its exploration is considered to be essential to the success of upcoming prevention and intervention programs in the area of body image and eating disorders. The role of shame, although widely studied in negative body image and eating psychopathology, is yet unknown regarding body appreciation. In this line, a main goal of this study was to explore the effect of external shame on body appreciation in a sample of Portuguese young adults. Also, taking into account the similarities between body appreciation and self-compassion, and since self-compassion is known as a powerful tool against the impact of shame on body image-related disturbances, this study also intended to test the role of self-compassion in the relationship between external shame and body appreciation. Results revealed body mass index and external shame as negative correlates, and self-compassion as a positive correlate of body appreciation. Also, path analysis showed that external shame holds a significant effect on body appreciation, both directly and indirectly. Specifically, this analysis revealed that self-compassion acts as a mediator between shame and body appreciation. Present findings seem to support the pertinence of programs to promote an affectionate and healthy relationship with one’s own body image, which may benefit from the target of shame and the inclusion of self-compassion practices.